Reorientation of the diagonal double-stripe spin structure at Fe1+yTe bulk and thin-film surfaces - Torben Hänke (Nature Portfolio, 2017)
Knowledge of the spin structure in parent compounds of unconventional superconductors is crucial for an understanding of the complex physics in these materials. Here, the authors report canted spin structure on the surface as well as on the thin film form of Fe1+yTe, different from the bulk.